2007
DOI: 10.1021/jf071696j
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic, Flavonoid, and Lutein Ester Content and Antioxidant Activity of 11 Cultivars of Chinese Marigold

Abstract: This study analyzed 11 Chinese cultivars of marigold to determine their major phytochemical contents and antioxidant activities. Dried marigold flowers were extracted with ethanol, ethyl acetate, and n-hexane and the extracts were analyzed by high-performance liquid chromatography-mass spectrometry and chemical methods to determine their lutein esters, phenolic and flavonoid contents, and antioxidant activity, respectively. The different cultivars of marigold showed considerable variations in their lutein este… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(60 citation statements)
references
References 27 publications
(42 reference statements)
3
50
4
Order By: Relevance
“…'Columbus Drange' and 'Lunar Drange' showed the lowest total phenolic content. Li et al (2007) reported that TPC and antioxidant activity of the ethanol extracts of 11 cultivars of Chinese marigold, which showed higher TPC and ABTS values than those observed in this study. The low activity obtained in our study, may be due to the effect of prolonged drying time.…”
Section: Phytochemical Content In Different Marigold Cultivarscontrasting
confidence: 55%
See 1 more Smart Citation
“…'Columbus Drange' and 'Lunar Drange' showed the lowest total phenolic content. Li et al (2007) reported that TPC and antioxidant activity of the ethanol extracts of 11 cultivars of Chinese marigold, which showed higher TPC and ABTS values than those observed in this study. The low activity obtained in our study, may be due to the effect of prolonged drying time.…”
Section: Phytochemical Content In Different Marigold Cultivarscontrasting
confidence: 55%
“…Synthetic methods have been developed for the production of lutein; however, the cost of production cannot compete with that of lutein isolation from marigold extracts (Fernández-Sevilla et al, 2010). Many studies have reported on the increase in the use of marigold extracts in functional food stuffs, cosmetics, and the pharmaceutical industry (Li et al, 2007;Hojnik et al, 2008). To date, marigold petals have also been one of the main industrial sources for lutein production.…”
Section: Introductionmentioning
confidence: 99%
“…Carotenoids such as lutein are an effective chain-breaking antioxidant because of their ability to quench singlet oxygen and scavenge peroxy radicals (Wang et al, 2006). However, there is a lack of information on the effects of dietary lutein on endogenous antioxidant enzymes in laying hens, although numerous in vitro studies have demonstrated that lutein has shown beneficial effects on antioxidant defense system against free radicals (Bhattacharyya et al, 2010;Hayes et al, 2009;Li et al, 2007). In agreement with our study, a dietary feeding of lutein in vegetable oils to rats increased lutein absorption, which in turn increased antioxidant enzymes, suggesting that lutein bioavailability might be a crucial factor that affects the antioxidant system in animals (Lakshiminarayana et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In literature, the lutein content of marigold flowers is usually reported for dry weight, and it varies widely depending on the variety. Examples of reported lutein contents (per dry matter) for different varieties of Tagetes erecta are 0.77-14.4 mg/g (Khalil et al 2012), 1.61-6.11 mg/g (Li et al 2007), 0.18-3.0 mg/g (Piccaglia et al 1998), and 10.3-17.0 mg/g (Deineka et al 2007). Deineka et al (2007) also measured the lutein content for fresh weight, and it was 2.10-2.97 mg/g with approximately 5-6 fold difference to content per dry weight.…”
Section: Resultsmentioning
confidence: 99%